BUSINESS FEASIBILITY ANALYSIS OF D’SWEETY LAYERS DESSERT CAKE - Putri, Berliana; Sonny, Sonny (President University, 2023)
Dessert is a food served as a cover after the main food that is often found in various countries, including Indonesia. In Indonesia, dessert is usually called